Assessment of Entrepreneurial Education and Diversity Management : A Gateway to Sustainable Development in Nigeria - Anthony, Kifordu Anyibuofu; Oshoke, Sadiq; Slyvester, Ohiomu (International Research Journal of Management, IT & Social Sciences, 2017)
The study assessed the contributions of entrepreneurship Education course in enhancing management/ entrepreneurial skills of informal entrepreneurs and diversity management. Informal entrepreneurs are those who passed through the technical/vocational schools and have certificates with which they are carrying out their entrepreneurship as a result of the fact that they are not able to move forward academically. Two research questions guided the study. The population, which was used as the sample for the study because of its small size, was 41 informal entrepreneurs in Delta North Senatorial District of Delta State. The instruments for data collection were a 140 item questionnaire. The mean was used for data analysis. Results showed that the entrepreneurship knowledge given to these informal entrepreneurs were adequate but are not re-enforced and some of the trade areas get less of what they are supposed to get. Attention also should be given to the technical aspect. The informal entrepreneurs in their fields of business have seen the entrepreneurship education as very important. Based on these, recommendations were made.